2018
DOI: 10.3389/fnbeh.2018.00308
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms for the Ketamine-Induced Reduction of P3b Amplitudes

Abstract: In specific dosages, the N-methyl-D-aspartate receptor (NMDA) antagonist ketamine can be used to model transient psychotic symptoms in healthy individuals that resemble those of schizophrenia. Ketamine administration also temporarily impairs cognitive functions, which can be studied by event-related potentials (ERPs). ERPs also allow dissecting what stages of information processing are affected by ketamine and what stages remain functional. For tasks requiring the differentiation of targets and non-targets, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 140 publications
0
1
1
Order By: Relevance
“…Most of this evidence comes from EEG studies demonstrating ketamine effects on several attention-related EEG components. In contrast to previous interpretations ( Schwertner et al, 2018 ), Rosburg and Schmidt (2018) suggested that the reduced P3 amplitudes found after ketamine treatment are better explained by working memory impairments than by a drug-related increase in task difficulty due to alterations of perceived stimulus salience. On the other hand, the influence of ketamine on high frequency oscillations does suggest a connection between glutamate, bottom-up attentional processing and selective attention ( Thiebes et al, 2018 ).…”
Section: Neuromodulatorscontrasting
confidence: 91%
See 1 more Smart Citation
“…Most of this evidence comes from EEG studies demonstrating ketamine effects on several attention-related EEG components. In contrast to previous interpretations ( Schwertner et al, 2018 ), Rosburg and Schmidt (2018) suggested that the reduced P3 amplitudes found after ketamine treatment are better explained by working memory impairments than by a drug-related increase in task difficulty due to alterations of perceived stimulus salience. On the other hand, the influence of ketamine on high frequency oscillations does suggest a connection between glutamate, bottom-up attentional processing and selective attention ( Thiebes et al, 2018 ).…”
Section: Neuromodulatorscontrasting
confidence: 91%
“…Thus, NMDA blockade affects early attentional processes as well as later voluntary control mechanisms ( Watson et al, 2009 ). Schwertner et al (2018) assumed that ketamine modulates EEG components by influencing stimulus discriminability (but see Rosburg and Schmidt (2018) for a different interpretation). This is in line with other research demonstrating that ketamine impairs the ability to both effectively gate the processing of sensory stimuli and process salient stimuli ( Krystal et al, 1999 ; Umbricht et al, 2002 ).…”
Section: Neuromodulatorsmentioning
confidence: 99%